Awareness of Age-Related Changes Among Middle-Aged and Older Adults: Longitudinal Trajectories, and the Role of Age Stereotypes and Personality Traits - Wettstein, Markus; Kornadt, Anna E.; Wahl, Hans-Werner (Frontiers in Psychiatry, 2022)
Awareness of Age-Related Change (AARC) describes to what extent people become aware of changes which they attribute it to getting older. So far it is unclear how different AARC dimensions change over time, to what extent these changes in different domains of AARC gains and losses are interrelated, and which predictors account for inter-individual differences in within-person longitudinal trajectories. Specifically, the extent to which individuals perceive age-related gains and losses might be shaped by their chronological age, their personality as well as by their general views on aging (i.e., their age stereotypes). We investigated changes in global and domain-specific AARC gains and losses over about five years in a sample of originally N = 423 participants aged 40 to 98 years at baseline. We analyzed the role of personality traits and age stereotypes for levels and changes of AARC, taking into account participants’ age at baseline and controlling for gender, education, and subjective health. Based on longitudinal multilevel regression models, we observed mean-level declines in most AARC gain domains. In contrast, perceived general AARC losses, as well as losses in health and physical functioning, in cognitive functioning and in social-cognitive/socio-emotional functioning remained, on average, stable over time. Baseline scores on AARC gains (global scale) were higher among individuals with higher neuroticism, openness, conscientiousness and more positive age stereotypes. Additionally, the association of higher neuroticism with higher AARC gain scores was stronger among individuals with more positive age stereotypes. Higher neuroticism and more negative age stereotypes also predicted higher baseline scores on AARC losses (global scale). At the same time, higher neuroticism was associated with a steeper decrease in AARC loss perceptions over time. Most of the intercorrelations within the intercepts and within the intra-individual trajectories of the different AARC domains were positive, but small in size. Our findings show the importance of considering trajectories of age-related gains and losses in parallel and across multiple developmental domains when investigating the subjective perception of the aging process. They also suggest that personality traits and general age stereotypes play a meaningful role for individual experiences of aging.